Environmental and Nutritional Factors Affecting the Production of Rubratoxin B by Penicillium rubrum Stoll - Hayes, A. Wallace (1970)
Rubratoxin B can be produced in a semisynthetic medium by Penicillium rubrum under varying environmental and nutritional conditions. Maximum production (552.0 mg/500 ml) was obtained with P. rubrum NRRL A-11785 grown in stationary cultures of Mosseray's simplified Raulin solution supplemented with 2.5% malt extract broth at ambient temperature. Zinc is required at levels of at least 0.4 mg per liter. In the absence of iron sulfate, there was a 50-fold reduction in rubratoxin B production but not in growth. No toxin was produced by this isolate in 5- or 7-liter fermentors.